Nutritional consequences of a fast food eating occasion are associated with choice of quick‐service restaurant chain. Issue 3 (28th July 2014) - Brindal, Emily; Wilson, Carlene; Mohr, Philip; Wittert, Gary
Abstract Aim The aim of the present study was to explore fast food purchasing behaviours and motivations and to assess whether eating at different quick‐service restaurant (QSR) chains affects macronutrient consumption of a fast food eating occasion. Methods A cross‐sectional computer‐based survey was completed by consumers at a local fair or via an external hyperlink. Consumers were at least 16 years and had purchased items from McDonald's, Hungry Jack's, KFC, Domino's or Red Rooster in Australia within the last 6 months. Custom‐written software captured the items consumed by the respondent, contextual data, reason for consumption and demographic information. Results Five hundred twenty‐three adolescents and adults (76.6% female; 81.3% Australian born) completed the survey. They reported commonly purchasing takeaway (69.7%) and from McDonald's (35.5%). Consumption was primarily convenience driven but varied by QSR. General linear models indicated that energy consumed (kJ; M ± SE) from fast food items varied significantly between chains, being higher at Hungry Jack's (4383 ± 138) and KFC (4277 ± 154) compared with Domino's Pizza (2725 ± 239) and McDonald's (3263 ± 124). Total saturated fat, sodium and percentage of energy from fat also varied significantly by QSR chain (all P < 0.001). Total energy consumed on one visit was positively associated with frequency of fast food consumption (P = 0.008). No demographic variable consistently associated with nutritional characteristics of the fast food eaten. Conclusions The nutritional implications of fast food consumption are not uniform across different QSR chains. To our knowledge, this is the first study to indicate an association between frequency of fast food consumption and energy intake at a fast food eating occasion.